Executive pay and shareholder litigation - Peng, Lin; Röell, Ailsa (Review of Finance, 2008)
Abstract The paper examines the impact of executive compensation on private securities litigation. We find that incentive pay in the form of options increases the probability of securities class action litigation, holding constant a wide range of firm characteristics. We further document that there is abnormal upward earnings manipulation during litigation class periods and that insiders exercise more options and sell more shares during class periods, but that this activity is largely driven by pre-existing option holdings of the managers. Our results suggest that option-based compensation may have the unintended side effect of giving executives an incentive to focus excessively on the short term share price.